Introduction (Scottish Archaeological Internet Reports, 2012)
Excavation took place in 2001 on the route of the St Fergus to Aberdeen gas pipeline. The cemetery was discovered during a watching brief on topsoil stripping of the pipeline easement and was subsequently fully excavated. Other discoveries included a ring ditch of uncertain date, three large pits of Late Neolithic or early Bronze Age date and a chipped stone scatter. Details of these are contained in the site archive.